Action and social alignment components of collaboration in SME business relationships. (2nd November 2019) - Payan, Janice M.; Padín, Carmen; Ferro, Carlos; Svensson, Göran
Abstract : While collaboration between business partners can generate enhanced outcomes, little is known about how the components of collaboration work. The action alignment component of collaboration includes both coordination (or joint activities) and economic satisfaction since they are both tangible concrete concerns. The social alignment component of collaboration includes sub-elements of both cooperation (or a spirit of willingness to work together) and non-economic satisfaction because both are intangible social concerns. Analysis of sub-elements of collaboration is important in clarifying key processes underlying successful collaboration. Structured equations modeling of surveys from qualified Spanish small-/medium-size enterprises about their suppliers was used here. Findings show that cooperation plays an important positive role in linking the two components of collaboration because while cooperation has an important positive association with a sub-element of social alignment (non-economic satisfaction), cooperation also has a positive direct association with both sub-elements of action alignment (coordination and economic satisfaction). As expected, coordination has a positive direct association with economic satisfaction but does not have a direct positive association with non-economic satisfaction. One key implication is managers should prioritize cooperation, or intangible social concerns of a relationship, over tangible concrete joint activities such as coordination, to improve outcomes with suppliers.